Human platelet antigen polymorphisms and the risk of chronic Chagas disease cardiomyopathy - Deborah Elzita do Carmo Corrêa; Christiane Maria Ayo; Jeane Eliete Laguila Visentainer; Eliane Papa Ambrosio-Albuquerque; Pâmela Guimarães Reis; Cinara Cássia Brandão de Mattos; Reinaldo Bulgarelli Bestetti; Luiz Carlos de Mattos; Ana Maria Sell (Platelets, 2020)
Human platelet antigen (HPA) polymorphisms are considered to be a risk factor for cardiac and vascular diseases, but the role of HPA in chronic Chagas disease cardiomyopathy (CCC) is not available. Therefore, the aim of this study was to investigate the association of HPA polymorphisms, HPA-1, HPA-2, HPA-3, HPA-5 and HPA-15, in the severity of left ventricular systolic dysfunction (LVSD) in CCC patients. For this, 229 CCC patients were separated into three groups: without LVSD, mild/moderate LVSD and severe LVSD. PCR-SSP was performed for HPA genotyping and the risk was assessed using SNPStats software. HPA-1 allele and genotype frequencies were lower in mild/moderate LVSD patients compared to other groups, without statistical significance. After stratified analyzes, the HPA-3a/3b genotype frequency was lower in women with severe LVSD compared to those without LVSD (OR:0.29; 95% CI: 0.10–0.84). In conclusion, HPA-3 variant could be a protection factor for CCC in the female patients.